Protecting organs-at-risk in cancer therapies through temporary organ displacement: a comprehensive review - Tino, Rance B.; Li, Michael; Heshmat, Amirreza; Suresh, Ayush; Guillaume, AnaSimone; Brock, Kristy K.; Odisio, Bruno C.; Koay, Eugene J. (Oncology Reviews, 2025)
Radiation therapy (RT) and locoregional ablation are cornerstones of modern oncology, yet their therapeutic potential is frequently limited by the challenge of sparing healthy organs-at-risk (OARs) from treatment-related complications. Temporary organ displacement (TOD) techniques directly address this issue by creating a physical separation using ‘spacers’ during treatment, thereby minimizing collateral damage while enhancing therapeutic precision. The clinical benefits, including improved tumor control, reduced morbidity, and enhanced survival, are documented across malignancies of the head and neck, thorax, abdomen, and pelvis. To create a unified framework for this evolving field, this comprehensive review provides a systematic classification of TOD techniques based on invasiveness, administration, device technology and the accompanying treatment mo`dality. Furthermore, we synthesize key historical and recent innovations, from non-invasive maneuvers to advanced surgical spacers, to contextualize current practices. Finally, we address barriers to standardization and highlight emerging concepts such as meta-materials, computational modeling, and digital twins, which provide promising avenues for enhancing personalized cancer care and patient outcomes.